Assesment of Disease Activity in Ankylosing Spondylitis: Comparison of Rapid3, Basdai, Basfi, and Asdas Scores in Routine Care - Cinar, Muhammet; Yilmaz, Sedat; Koca, Suleyman Serdar; Erdem, Hakan; Pay, Salih; Yazici, Yusuf; Simsek, Ismail (Wiley, 2011)
[Abstract Not Available]
75th Annual Scientific Meeting of the American-College-of-Rheumatology (ACR) / 46th Annual Scientific Meeting of the Association-of-Rheumatology-Health-Professionals (ARHP) -- NOV 04-09, 2011 -- Chicago, IL